Acute Maternal Stress Disrupts Infant Regulation of the Autonomic Nervous System and Behavior: A CASP Study - Isabelle Mueller (Frontiers Media S.A., 2021)
Exposure to maternal stress is assumed to influence infant health and development across the lifespan. The autonomic nervous system (ANS) is especially sensitive to the effects of the early caregiving environment and linked to predictors of later mental health. Understanding how exposure to maternal stress adversely affects the developing ANS could inform prevention. However, there is no agreed upon definition of maternal stress making its study difficult. Here we use the Caretaker Acute Stress Paradigm (CASP) to study the effects of maternal stress in an experimentally controlled laboratory setting. The CASP has 5 episodes, a natural play, followed by a caretaker stressor (or control) condition, another play, a classic still face episode, followed by another play. A total of 104 4-months-old infants and their mothers were randomly assigned to either the caretaker-stress or caretaker-control condition. Changes in behavior, heart rate (HR), and respiratory sinus arrhythmia (RSA) before and after the introduction of the stressor (or control condition) were recorded and compared. Infants in the maternal stress condition showed significantly more behavioral distress [X2 = (1, N = 104) = 4.662, p = 0.031]. Moreover, infants whose mothers were in the stress condition showed an significant increase in heart rate after the caretaker condition [F(1, 102) = 9.81, p = 0.002]. Finally we observed a trend to faster RSA recovery in infants of the control condition [F(1, 75) = 3.539, p = 0.064]. Results indicate that exposure to acute maternal stress affects infant regulation of the autonomic nervous system and behavior.